Hubungan Caring Perawat Dengan Kepuasan Pasien Rawat Inap Di Rumah Sakit - Nahrul Hayat; Asfri Sri Rahmadeni; Marzuki Marzuki (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
Caring nurses are very important in meeting patient satisfaction, this is one indicator of the quality of service in a hospital. Nurses are people who become one of the keys in meeting patient satisfaction. Therefore, caring nurse behavior can have an effect on quality service to patients. Some studies conducted in Indonesia show that caring is still lacking for patients in hospitals as much as 50% show poor caring. Patient satisfaction is influenced by caring nurses in serving patients in hospitals. The purpose of this study was to analyze the relationship between caring nurses and patient satisfaction in the inpatient room. This study is a cross sectional analytic study and purposive sampling technique with a sample of 67 patients, collecting data using a questionnaire.The Chi-Square test results showed a significant relationship between caring nurses and patient satisfaction in the inpatient room with a p value of 0,045 (Î± = 0,05). Nurse caring attitude greatly affects patient satisfaction so it is expected that nurses or other health workers can be more sensitive, be responsive and respond well to patient complaints and show sincere care in helping patients recover